An online detection system of energy efficiency for intelligent manufacturing. (November 2021) - Ren, Jianqiang; Zhang, Lingjuan; Feng, Yue; Wan, Lingyu
Abstract: Online detection of energy efficiency automatically has important significance for evaluating new production lines and detecting the performance of existing production lines in modern intelligent manufacturing and smart industry. To solve the shortcomings of existing detection systems, a novel online detection system of energy efficiency is proposed in this paper. Within a time interval, the proposed system detects the production quantity and the energy consumption of the production line by a production quantity detection module and a power consumption sensing module, then calculates and obtains the production efficiency during the period and displays to users by output module. Experimental results show that the proposed system has high practical value.